ANALISIS QOS (QUALITY OF SERVICES) JARINGAN INTERNET BERBASIS WIRELESS TELKOM INDIHOME PADA KANTOR WALIKOTA BENGKULU - Utama, Fiqri Saputra; Siswanto, Siswanto; Kanedi, Indra (Jurnal Media Infotama, 2024)
This research aims to: determine the quality of service of the WLAN network at the Bengkulu Mayor's Office. QoS (Quality of Service) is the ability to provide the performance of a computer network in providing services to applications on the computer network so as to determine the level of satisfaction of users who use the network.This research is quantitative research which refers to research methods according to Polit D.F and Hungler B.P. The research was carried out by monitoring the WLAN network on access points designated as samples in each department in the Bengkulu Mayor's Office using WireShark software. The data collection techniques used were observation, interviews, literature study and monitoring. From the results of the research carried out, it can be concluded that the quality of WLAN network service at the Bengkulu Mayor's Office is included in the Adequate category according to TIPHON.